Polish Independent Press Review, no. 3 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). "Zona": A New Central European Publication / by Anna Pomian"Zona" is a sociopolitical journals devoted to the problems of East and Central Europe, containing mostly relevant reprints from other journals, both East and West. Printed in Poland, its editors claim that it is published in several East and Central European languages. Some Political Views and Insights of Polish Children / by Anna PomianPolish children's views on the current situation in Poland were the subject of a recent article in the independent press; several publications cater for the youngest generation in opposition. Trends in the Political Opposition / by Anna PomianA recent article in the Polish Independent press suggested that Polish opposition groups fell into three basic categories. A Quick Quiz / by Anna PomianAn independent publication issued in Gdańsk recently gave its readers a quiz to test their knowledge of Polish affairs. Profiles of Major Independent Polish Publications: "Wola" / by Michał Kołodziej"Wola - Pismo Międzyzakładowego Komitetu Koordynacyjnego" is published each week in Warsaw by Solidarity members from Warsaw factories.